Pengaruh Indeks Harga Konsumen, Jumlah Uang Beredar, Produk Domestik Bruto, Suku Bunga, dan Neraca Pembayaran Terhadap Nilai Tukar Rupiah - Rofi'i, Yulianto Umar (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This study aims to analyze the relationship between various assumed economic variables and exchange rate fluctuations of the Rupee against the US dollar. The variables considered include the logarithmic difference of the consumer price index of Indonesia and the United States, the logarithmic difference of the money supply of Indonesia and the United States, the logarithmic difference of the gross domestic product of Indonesia and the United States, the logarithmic difference of the Indonesian and US interest rates and the logarithm of the Indonesian balance of payments. The data analysis results show that only the difference between the logarithm of the gross domestic product of Indonesia and the US and the difference between the logarithm of the interest rates of Indonesia and the US have a significant influence on the change in the exchange rate of Indonesia rupiah. The R-squared of 61.6% shows that the observed variation in the dependent variable can be explained by the independent variables, while the remaining 38.4% is influenced by other factors. The conclusion of this study is that the difference in change in the logarithm of gross domestic product and the difference in the logarithm of interest rate have a significant impact on the volatility of the rupee exchange rate.